Nrf-2-driven long noncoding RNA ODRUL contributes to modulating silver nanoparticle-induced effects on erythroid cells. (June 2017) - Gao, Ming; Zhao, Beibei; Chen, Minjun; Liu, Yun; Xu, Ming; Wang, Zhe; Liu, Sijin; Zhang, Chengdong
Abstract: The biosafety and biological effects of silver nanoparticles (AgNPs) on human health attract increasing concern. Although considerable studies have been performed to reveal the molecular mechanisms responsible for AgNP-induced effects, the current understanding mainly focuses on oxidative stress-associated signaling pathways activated by Ag particles and/or Ag ions. However, the molecular bases underlying the activation of these stress signaling pathways have not been thoroughly elucidated yet. In the current study, we aimed to shed light on the molecular bases of AgNP-induced effects on erythroid cells from the perspective of long noncoding RNAs. We identified a long-noncoding RNA molecule, ODRUL, which was substantially enhanced in K562 erythroid cells responding to AgNPs, coupled to accelerated cell death. Further, we uncovered oxidative stress-driven Nrf2 transcriptionally promoted ODRUL expression in K562 cells. Downstream of Nrf2-ODRUL activation by AgNPs, ODRUL was recognized to interact with PI4Kα protein to modulate the activities of its targets AKT and JNK. As a result, the Bcl-2 level was negatively regulated by PI4K-AKT/JNK signaling under AgNP-induced stress, leading to enhanced cell death. Together, our findings unearthed that Nrf2-mediated lncRNA ODRUL was indispensable for AgNP-induced toxicity in erythroid cells through regulation of AKT/JNK-Bcl-2 signaling dependent on a physical interaction with PI4Kα. Thus, this study would open a new path to depict the molecular bases of AgNP-induced effects on erythroid cells. Highlights: LncRNA ODRUL expression is promoted by Nrf2 under AgNP-induced oxidative stress. ODRUL interacts with PI4Kα protein to impede its pro-survival function. AKT and JNK are the downstream targets of ODRUL/PI4Kα responding to AgNPs. Bcl-2 is a final executor of ODRUL/PI4Kα signaling to modulate cell death upon AgNP stress.